Economic valuation for recreational services of the Permanent Forest Estate in Kuala Kubu Bharu: a travel cost analysis - Abdullah, Azamil; Mohammad Afandi, Syamsul Herman; Shuib, Ahmad; W Mohamad, Wan Norhidayah (Human Resource Management Academic Research Society, 2023)
Kuala Kubu Bharu (KKB), located in the northeastern part of Selangor, is a popular ecotourism site among visitors from Klang Valley and the neighbouring states. Visitors participate in several outdoor recreational activities in the surrounding Permanent Forest Estate (PFE) in KKB. The increasing number of tourists visiting KKB has raised the attention of local authorities to justify sustaining the natural recreational resources in KKB. However, the value of the benefits of recreational use of the forest has not been determined. Using the Travel Cost Method (TCM), data from visitors to KKB were collected to estimate the value of the natural recreational resources in KKB using consumer surplus. Based on the total number of visitors to KKB in 2019, the estimated consumer surplus is RM1,179,094.18. On the other hand, the estimated consumer surplus per tourist for each visit to KKB is RM6.38. The estimated consumer surplus per tourist per visit can be applied as the price for conserving the PFE in KKB.